Higher Education with Disabilities Policy: Ensuring Equality Inclusive Education in Indonesia, Singapore and United States - Wardani Amnesti, Sheila Kusuma; Jundiani, Jundiani; Zulaichah, Siti; Mohd Noh, Mohd Shahid; Fitriyah, Lailatul (Lembaga Contrarius Indonesia, 2023)
There are still relatively few people with disabilities who complete their education up to the university level in Indonesia. In contrast, Singapore and the United States are known for their high levels of innovation, especially in promoting equality in education. Three countries—Indonesia, Singapore, and the United States—share a common commitment to realizing the protection of disability rights. This research employs normative legal research methods, utilizing both statutory and comparative approaches. The findings of this study reveal that Singapore's universities have the highest percentage of disability-friendly institutions, with approximately 60% of colleges maintaining specialized Disability Services units. In the United States, only 4.7% of colleges offer Disability Services, while in Indonesia, the figure stands at 1.48%. Substantial, structural, and cultural challenges persist in all three countries when it comes to fulfilling the right to education, particularly concerning funding policies. Each nation needs to cultivate a culture of anti-discrimination in disability education. Notably, Indonesia has yet to implement an inclusive curriculum in higher education. This paper holds significant importance in the context of improving educational services for individuals with disabilities, ultimately contributing to the realization of equality in the education system.